Cargo port choice equilibrium: A multi-perspective look at shippers' port choice. (October 2021) - Talley, Wayne K.; Ng, ManWo
Highlights: Traditionally, cargo port choice has been studied from the perspective of port users. Recently, studies focusing on the perspective of port service providers have appeared. Cargo port choice should be examined from both perspectives, simultaneously. Cargo port choice equilibrium is proposed to model joint choice. Prior findings in the port choice literature might no longer be valid without further qualifications. This research generalizes, unifies and extends the prior shippers' port choice literature. Abstract: Traditionally, cargo port choice has been investigated from the perspective of port users. More recently, studies on cargo port choice from the perspective of the port service providers have appeared. Irrespective of the perspective taken, the common element in these studies is that they focus on one perspective at a time. In this paper, it is postulated that cargo port choice should really be examined from both perspectives, simultaneously, as cargo port choice is made by both users and providers of cargo port services. The port users we will focus on in this paper are the shippers. To model this simultaneous choice, a new modeling framework is proposed, i.e. cargo port choice equilibrium. This new framework enables policy makers and other maritime industry stakeholders to evaluate the network-wide impact (i.e. across all cargo ports) of a range of policy measures while considering the choices by both shippers and port service providers. One key consequence of our equilibrium model is that prior findings in the port choice literature might no longer be valid without further qualifications. Overall, this paper generalizes, unifies and extends a segment of the port choice literature.